Utvärdering av flygbildstolkning för uppskattning av beståndsvariabler och åtgärdsförslag i ungskogar : en studie på Korsnäs Skog och Bergvik Skog AB i västra Dalarna - Andersson, Lars (SLU/Dept. of Forest Resource Management, 2008)
In Korsnäs district Dala Väst there were problems with information concerning their younger forests, mainly those in pre-thinning stage. They were divided into large, heterogeneous stands with often poor stand data quality. In 2006 an aerial photo interpretation of the young forests was conducted to fix these problems. Necessary information to get from the interpretation were silvicultural management suggestions, new stand delineation and new stand data. This thesis is supposed to evaluate the quality and usability of the interpreted data.